Syngas Characteristics and Energy Performance of Betung Bamboo (Dendrocalamus asper) Pellets in a Downdraft Gasifier - Chrisyan Fito Simamora; Bugae Park; Bainah Sari Dewi; Wahyu Hidayat (Green Insight Solutions, 2026)
Indonesia currently faces a significant energy challenge, with 85% of national needs met by declining fossil fuel reserves. While biomass is a sustainable alternative, empirical data on the performance of betung bamboo (Dendrocalamus asper) pellets in downdraft gasifiers remains limited. This study aims to analyze the evolution of syngas composition, determine the lower heating value (LHV), and characterize the proximate properties of both the feedstock and the resulting residue. The research utilized a sample size of 20 kg of betung bamboo pellets in a 15-kWh downdraft gasifier operated for 60 minutes. Syngas components were monitored in real time using a portable infrared syngas analyzer, while proximate analysis determined moisture content (MC), volatile matter (VM), ash content (AC), and fixed carbon (FC). The results revealed an average syngas composition of 13.62% carbon monoxide (CO), 8.65% hydrogen (H₂), 2.55% methane (CH₄), 13.28% carbon dioxide (CO₂), and 1.64% oxygen (O₂), yielding a total combustible gas fraction of 24.82%. The average LHV was 887.57 kcal/m³, with a peak value of 981.45 kcal/m³ recorded as the reactor reached steady-state conditions. Proximate analysis indicated effective thermochemical conversion, as VM decreased from 74.11% in the pellets to 17.61% in the ash by-product, while AC increased from 12.02% to 73.09%. Furthermore, FC declined from 6.76% in the pellets to 4.63% in the residue. This study concludes that betung bamboo pellets are a highly suitable and promising renewable energy feedstock for small-scale applications in Indonesia, offering a scientific basis for decentralized biomass energy systems.